In situ reconstruction of an MRSA-infected paravisceral aortic pseudoaneurysm with cryopreserved aortic allograft - Banga, Peter (Interv Med Appl Sci, 2019)
OBJECTIVES: Treatment of paravisceral aortic infections poses several challenges because standard therapy with excision of all infected tissues and extraanatomic reconstruction is frequently not possible without jeopardizing visceral perfusion. In situ reconstruction with rifampin-soaked prosthetic graft or endovascular repair with stent grafts runs the risk of reinfection. We present a case of a paravisceral aortic infection, where cryopreserved allograft was used for the reconstruction of the aorta. METHODS: Medical documentation and CT angiography studies were retrospectively reviewed for a patient in a tertiary care center. RESULTS: A 62-year-old male patient presented with an infected pseudoaneurysm of the paravisceral aorta at the level of the celiac artery. He had previously undergone multiple orthopedic surgical interventions and developed methicillin-resistant Staphylococcus aureus infections. We successfully repaired the paravisceral pseudoaneurysm with excision of all infected tissues and in situ aortic replacement with a cryopreserved allograft. CONCLUSION: In case of infected aortic pseudoaneurysm, the use of cryopreserved aortic allograft is a reliable choice for reconstruction of the aorta.